Prospects for change in the basic education and high school. Ecuador: 2007-2013 (Praxis Educativa, 2015)
This article deals with the Ecuadorian education system in the period 2007- 2013. The evaluation, applauses or critics and even the complaints about the education development, under any government, can be made at least under two perspectives: one of them aimed at highlighting the achievements and/or weaknesses –external critics– and, the other that points to what was planned or the government offered to manage, and the effective accomplishments –internal critics. Both of them must be complemented with the analysis of the objective conditions and with the available resources for the projects and programs –contextual critics– and with the references to the historical transcendence or consequent prospective generated by the implemented reforms –historical critics–. The evaluation can also aim at the processes and determine, with quantitative indicators, the tendencies, and in that way, make the plans for future development. Each of these critics requires to be subjected to ideological critics and self-criticism, tasks that author and reader should do.
Keywords: education system; critical revision; future perspectives